Impact of deamidation on the physicochemical properties and air-water interfacial behaviour of gliadin nanoparticles - Moraveji, Maryam; Sadat, Azin; Joye, Iris J. (Frontiers in Soft Matter, 2022)
Gliadin due to its low water solubility is excellently suited to make biopolymeric nanoparticles through liquid antisolvent precipitation. These gliadin nanoparticles (GNPs) can be utilized to populate and stabilize interfaces. Gliadin, by nature a protein that carries a low charge, can be altered by deamidation. Deamidation effectively alters the physicochemical properties of gliadin through decreasing the protein’s isoelectric point (IEP). The objective of this study is to explore the effect of different degrees of deamidation on gliadin nanoparticle (interfacial) characteristics. Besides altering the physical stability of GNP suspensions, deamidation did alter the functionality of GNPs as interfacial agents. GNP behaviour at the air-water interface is substantially impacted by pH. Particles made with untreated and deamidated gliadin exhibited a greater tendency to adsorb and form strong viscoelastic films at the air-water interface and better foam structures closer to their IEP. The combination of SEM, confocal Raman microscopy and drop tensiometry provides unique insights in the dominant gliadin structures and interactions at the interfacial film. This study provides crucial insights into the potential of deamidation to tailor gliadin and GNP properties for specific food applications.